(3EOGQI GdHfhc (B:s (3eONd cej h GSJQGJjLj eYGUQ (B/s - (3GdMSjfj, adGM MSfs; (3GdOhQj, eDjO YHO GdQMefs ((3YeGf(B: s (3OGQ hGFd ddfTQ h GdJhRjY(B, s, 2008)
(3GdaUd GdChd (B: (3eaGgje eGdjI heUQajI CSGSjI(B-(3GdaUd GdKGfj (B: (3GdHfhc, GdCgejI, GdhXGFa, GdCgOGa(B-(3GdaUd GdKGdK (B: (3YedjGJ GdEOGQI GdGSJQGJjLjI aj GdHfhc(B-(3GdaUd GdQGHY (B: (3SjGSI JNUjU GdehGQO GdeGdjI aj GdHfhc(B-(3GdaUd GdNGeS (B: (3EOGQI QCS GdeGd GdeeJdc(B-(3GdaUd GdSGOS (B: (3EOGQI GdSjhdI GdeUQajI(B-(3GdaUd GdSGHY (B: (3GdGSJQGJjLjGJ GdCSGSjI dEOGQI hLPH GdhOGFY GdeUQajI(B-(3GdaUd GdKGef (B: (3GdGSJQGJjLjI GdEbQGVjI ddefTBJ GdeGdjI hGdeUQajI(B-(3GdaUd GdJGSY (B: (3GSJQGJjLjI EOGQI eMaXI GdGSJKeGQGJ GdeUQajI(B-(3GdaUd GdYGTQ (B: (3TQcGJ GdJCejf hGdHfhc GdESdGejI(B-(3GdaUd GdMGOj YTQ (B: (3YedjGJ GdQbGHI hJbhje GdCOGA aj GdHfhc(B.s
(3HjHdjhZQGajG U(B.s
Keywords: (3GOGQI GdHfhcs; (3GdeUGQa hGdUjQag(B--(3JfXje hGOGQgs; (3Ydhe GLJeGYjIs